PENGARUH HARGA, KUALITAS PRODUK, KUALITAS LAYANAN DAN KELENGKAPAN PRODUK TERHADAP LOYALITAS PELANGGAN UMKM (STUDI PADA TOKO PERABOT ALUMANIUM â€œSASâ€ RANTAUPRAPAT) - Simanjorang, Elida Florentina Sinaga; Chindi, Chindi (Universitas Labuhanbatu, 2021)
This study aims to discuss the effect of price, product quality, service quality and product completeness on customer loyalty at the Sinar Aluminum Service (SAS) Rantauprapat Store. The population in this study are customers who have made a purchase transaction and a sample of 67 respondents with a simple random sampling technique, which means that all populations have the same opportunity to become respondents. Data analysis using Multiple Linear Regression Analysis, t-Test, F-Test, and Determinant Coefficient Test. The results showed that based on the t-test that partially all independent variables had a positive and significant effect on the dependent variable. The F-test results show that simultaneously all independent variables have a positive and significant effect on the dependent variable. In the determinant coefficient test, the Adjusted R Square value is 0.400 or 40%, which means that customer loyalty can be explained by the variables of price, product quality, service quality and product completeness, while the remaining 60% can be explained by other variables not examined in this study. Customer loyalty is very important for UMKM in order to maintain the continuity of their business activities. The existence of the best price, product quality, service quality and completeness of the product will arouse the enthusiasm of customers to transact again, even further introducing the product to others.